Elite Theory and the 2003 Iraq Occupation by the United States How US Corporate Elites Created Iraq's Political System - Nouri, Bamo (Routledge Studies in US Foreign Policy Ser., 2021)
Cover -- Half Title -- Series Information -- Title Page -- Copyright Page -- Table of Contents -- Figures -- Acknowledgements -- Introduction -- Questioning the US Self-Concept - Substance Versus Image -- Elite Theory and the Examination of US Decision-Making in Iraq -- US Elites in Iraq -- Iraq's Elitist Political System as a Result of Self-Serving Corporate US Elites -- The Social Sources of US Power -- Accountability in Foreign Policy -- The Approaches - 'Power Structure Research' -- Combining Power Structure Studies With Studying Actual Decision-Making -- 'The Decisional Approach' -- Outlines -- Notes -- 1 Theories and Methods -- Imperialism -- The Role of Constructed Discourse On US Foreign Policy: 'Americanism' in the US Self-Concept and Ideology -- Definition of Imperialism for the Purpose of this Study -- US Democracy Promotion -- Elite Theory -- Rival Theories -- Importance of Elite Theory -- Definition of the 'Elite' -- Methods -- Self-serving Elites Or Genuine Democracy Promotion? -- Studying Power - the Concepts Relating to 'Power Structure Research' -- Membership Network Analysis and Content Analysis -- Approaches: Positional, Reputational and Decisional -- Importance of 'Power Structure Research' for Elite Theory -- Selection of Elites - Criteria -- Thirty-seven Bush Elite Decision-Makers -- Case Study Approach -- Methods in Structural Order -- Notes -- 2 Backgrounds, World-Views and Networks in the George W. Bush Elite -- Aims and Structure of the Chapter -- George W. Bush -- Karl Rove -- Condoleezza Rice -- Richard Bruce Cheney -- Paul Dundes Wolfowitz -- Lewis Paul Bremer III -- Early Analysis of the Selected Six -- Place of Birth and Social Backgrounds -- Ivy League Institutions and Education Backgrounds -- Think-tanks -- The Corporate Ties -- Previous Political Positions.